Psychosocial determinants of quit motivation in older smokers from deprived backgrounds: a cross-sectional survey - Smith, Pamela (BMJ Open, 2021)
OBJECTIVES: To identify psychosocial determinants of quit motivation in older deprived smokers. The evidence may be used to optimise smoking cessation interventions for the target population. DESIGN: Cross-sectional survey using online recruitment methods including Facebook-targeted advertising. SETTING: UK, 2019. PARTICIPANTS: Current smokers aged 50 years or older and from a socioeconomically deprived background. MAIN OUTCOME MEASURES: Measures included motivation to stop smoking, smoking history, perceived social support, self-efficacy for quitting, self-exempting beliefs and lung cancer risk perception. Multivariable regression was used to analyse factors associated with quit motivation. RESULTS: Of a total 578 individuals who consented to take part, 278 (48.1%) did not meet the inclusion criteria. Of the 300 eligible participants, most were recruited using Facebook (94.0%), were aged 50–64 years (83.7%) and women (85.7%). Most participants were renting from a housing association (72.0%) and had low education (61.0%). Higher motivation to quit was statistically significantly associated with a higher intensity of previous quit attempts (p=0.03), higher quit confidence (p=0.01), higher smoking self-efficacy (p=0.01), a lower risk-minimising beliefs score (p=0.01) and using traditional nicotine replacement therapy (NRT) when trying to stop smoking or cut down (p<0.001). CONCLUSION: Older smokers from deprived backgrounds face complex barriers to quitting smoking. Interventions are needed to increase self-efficacy for quitting, modify risk-minimising beliefs and target elements of previous quit attempts (ie, the use of NRT) that are associated with motivation to stop smoking.